A Critique on “Populist” and “Security-Oriented” Legal Policy in Curbing COVID-19 Related Crimes - Khaghani Esfahani, Mahdi (Bioethics and Health Law Journal (BHL), 2025)
The rapid and dire spread of the COVID-19 pandemic has had profound consequences for the various aspects of the human life worldwide and has distorted the coherence and rationality of governments’ behavior in the face of the crisis. Similar to the severe restriction of human rights under the pretext of securing political and human security following the terrorist attacks of September 2001, the pandemic of the new disease has been used as an excuse by some governments to ride on the wave of fear pumping into society under public scrutiny; to suppress social movements; to cover up the health system’s monitoring of the disease, to gather a wide range of people’s private information; to take advantage of the media’s focus on the news of this pandemic and the turmoil of the public mind, to refrain from fair trial and restorative justice into the old retributive punishments, not honoring the victim and violating the human rights of the offender and increasing judicial and security powers by relying on “zero tolerance” and “law and order” crime control strategies. This article, using discourse analysis method along with case studies, analyzes two inappropriate strategies-securityism and populism- in the criminal policy of some governments since the emergence of the pandemic in four levels: Factors, effects, consequences and strategies to eliminate.